Microplastics alter the toxicity of benzo[a]pyrene in a mangrove oyster: An integrated biomarker approach - Raphael Vitorino Gloria Giannetto; Jennifer Barbosa dos Santos; Rodrigo Brasil Choueri; José Hérelis Carnaúba; Ana Cecilia Rizzatti de Albergaria-Barbosa‬; Fábio Ruiz Simões; Camilo Dias Seabra Pereira; Caio Rodrigues Nobre; Paloma Kachel Gusso-Choueri (Marine Environmental Research, 2026)

New extensions of Cell2Fire software for fire risk analysis and evaluation in Chilean forests - Jaime Carrasco-Barra; José Ramón González-Olabarria; Camilo Matus-Olivares; Felipe Ulloa-Fierro; Felipe Soto; David Palacios; Rodrigo Mahaluf; Felipe de la Barra; Carolina Espinoza; Matías Vilches; Matilde Rivas; Fernando Badilla; et al. (Environmental Modelling & Software, 2026)

Meta-analysis of woody plant diversity and aboveground biomass stock co-benefits across Amazon agroforestry systems - Thamires Campos de Almeida; Silvio Nolasco de Oliveira Neto; Arthur da Cruz Silva; Rodrigo Gomes Gorsani; Lorena Evangelista Fernandes; Sebastião Venâncio Martins; Mehdi Heydari; Andrés Iván Prato; Lisandra Mendes Louzada-Camilo; Ana Luiza Rangel; Jamerson Souza da Costa; Alisson Lopes Rodrigues; et al. (Agroforestry Systems, 2026)

Synthetic Resistance Inducers: an Alternative to Fungicides for Controlling Gaeumannomyces Graminis in Rice - Iván Rodrigo Urrego-Velez; Cristhian Camilo Chávez-Arias; Sandra Gómez-Caro; Hermann Restrepo-Díaz (Journal of Crop Health, 2026)
Two field experiments were conducted to assess the effects of individual and combined resistance inducers (RIs) sprays on disease severity, physiological performance, and yield components to control crown sheath rot caused by Gaeumannomyces graminis in rice. In the first experiment, individual applications of cinnamaldehyde (CA), botanical extract (BE), nano-silicon (SiNPs), and chitosan (Chi) were compared with fungicide treatment and an untreated control. The second experiment focused on the efficacy of RIs combinations. Disease severity, area under the disease progress curve (AUDPC), leaf gas exchange properties, chlorophyll fluorescence parameters, and agronomic variables were measured in both the experiments. The results showed that individual and combined RIs treatments reduced disease severity [~3.3 and ~3.4%, respectively] and AUDPC [~85 and ~95, respectively] compared to the untreated control ((individual: 5.20 and 198); (combined: 5.40 and 178)), with RIs efficiency similar (35%) to that of fungicide treatment. RIs application improved leaf photosynthetic rate, photosystem II efficiency, and relative chlorophyll content under biotic stress conditions. Grain yield and efficiency per unit area (EUA) were also enhanced by the RIs treatments, particularly BE (10812 kg · ha −1 ; 83.99 kg rice paddy · m −2 · d −1 ) and SiNPs + Chi + BE + CA (~9600 kg · ha −1 ; ~73 kg rice paddy · m −2 · d −1 ) in comparison with untreated plants [(E1:8283 kg · ha −1 ; 62.42 kg rice paddy · m −2 · d −1 ) and (E2:7475 kg · ha −1 ; 54.32 kg rice paddy · m −2 · d −1 )]. These findings suggest that the foliar application of synthetic RIs during the vegetative stage can be an effective component of integrated disease management strategies for crown sheath rot in rice, potentially reducing the reliance on fungicides while maintaining crop productivity and promoting sustainable disease control.

Cationic Bacteriochlorin in the photodynamic inactivation of microorganisms - Juliana Kafka Bilha; Priscila Romero Mazzini Pereira; Laura Beatriz dos Santos Costa; Andres Camilo Acosta Acevedo; Clovis Wesley Oliveira de Souza; Michel Rodrigo Zambrano Passarini; Marciana Pierina Uliana (Brazilian Journal of Microbiology, 2025)

Bird–window collisions: A comprehensive dataset for the Neotropical region - Augusto João Piratelli; Bianca Costa Ribeiro; Wesley Dáttilo; Luis‐Bernardo Vázquez; Anelisa Ferreira de Almeida Magalhães; Edna Maria Gomes Cavalcante; Eric Silva; Giovanna Viana Cruz; Gisele Regina Ruy; Juliana Laurito Summa; Júlia Milan; Leila Pedrosa; et al. (Ecology, 2025)
Our primary objective was to compile a comprehensive dataset on bird–window collisions throughout the Neotropical region, including both published and unpublished sources. On May 12, 2020, we extensively disseminated invitations to provide data via email and social media platforms. By providing a template worksheet, we required standardized information from collaborators to complete and register their data. To better understand how these data were acquired (e.g., incidental observations and systematic procedures), we sent out a survey to all collaborators. We established rigorous validation criteria for data inclusion and conducted thorough curation procedures to ensure accuracy. After the filtering process, we compiled a total of 4103 bird–window collision reports. These came from 11 Neotropical countries, dating from 1946 to 2020, and revealing distinct regional patterns and potential seasonal patterns. The five most frequent orders were Passeriformes (2451), Columbiformes (520), Apodiformes (377), Psittaciformes (202), and Piciformes (186). Data on bird–window collisions were collected through a local specific systematic protocol (1419), by chance (1252), by government agencies (742), and by other approaches (632), while a few reports were collected by unknown procedures (58). The volume of records across months in our dataset suggests that there may be temporal patterns, with peaks: the first one in March–April and the second one in October–November, which seem to align with the major migration and reproduction seasons. This dataset represents the first comprehensive effort in the Neotropical region focused on bird–window collision data, providing valuable insights for further scientific advancements and conservation policies. The data are free from copyright or proprietary restrictions. Please cite this data paper when using the data in publications or scientific presentations.

Classification of synoptic weather patterns associated with extreme wave events in different regions of Western South Atlantic - Matheus Bonjour Laviola da Silva; Danilo Couto de Souza; Fernando Tulio Camilo Barreto; Rodrigo Tecchio; Renan de Freitas Pimentel dos Anjos; Carolina Barnez Gramcianinov; Ricardo De Camargo (Natural Hazards, 2025)

Parameterization of waves interacting with homogenous permeable breakwaters: Integrating physical and numerical models with machine learning - B. Rodrigo Covarrubias-Contreras; Alec Torres-Freyermuth; Camilo Rendón-Valdez; Christian M. Appendini; Ernesto Gray (Ocean Engineering, 2025)

Exposure to microplastics contaminated with pharmaceuticals and personal care products: Histological effects on Ucides cordatus - Letícia Fernanda da Silva; Caio Rodrigues Nobre; Beatriz Barbosa Moreno; Camilo Dias Seabra Pereira; Alexandre Rodrigo Nascimento Gonçalves; Nathalia Sales Soares do Nascimento; Gabriela Pustiglione Marinsek; Renata de Britto Mari; Fábio Ruiz Simões; José Hérelis Carnaúba; Rodrigo Brasil Choueri; Paloma Kachel Gusso-Choueri; et al. (Science of The Total Environment, 2024)

Pharmaceuticals in the environment: A strategy for prioritizing molecules of environmental concern - Taciana Guarnieri; Jacqueline R. Nascimento; Marcus Leonan; Pedro R. Brandão; Camilo Dias Seabra Pereira; Rodrigo Brasil Choueri; Elisa Hardt; Maria Lourdes L. Moraes; Leandro A. Calixto; Vanessa J. Pereira; Levi G. Oliveira; Sherlan Guimarães Lemos; et al. (Chemosphere, 2024)

Camera trap surveys of A tlantic F orest mammals: A data set for analyses considering imperfect detection (2004–2020) - Ingridi Camboim Franceschi; Rubem Augusto da Paixão Dornas; Isabel Salgueiro Lermen; Artur Vicente Pfeifer Coelho; Ademir Henrique Vilas Boas; Adriano Garcia Chiarello; Adriano Pereira Paglia; Agnis Cristiane de Souza; Alana Rafaela Borsekowsky; Alessandro Rocha; Alex Bager; Alexander Zaidan de Souza; et al. (Ecology, 2024)
Camera traps became the main observational method of a myriad of species over large areas. Data sets from camera traps can be used to describe the patterns and monitor the occupancy, abundance, and richness of wildlife, essential information for conservation in times of rapid climate and land‐cover changes. Habitat loss and poaching are responsible for historical population losses of mammals in the Atlantic Forest biodiversity hotspot, especially for medium to large‐sized species. Here we present a data set from camera trap surveys of medium to large‐sized native mammals (>1 kg) across the Atlantic Forest. We compiled data from 5380 ground‐level camera trap deployments in 3046 locations, from 2004 to 2020, resulting in 43,068 records of 58 species. These data add to existing data sets of mammals in the Atlantic Forest by including dates of camera operation needed for analyses dealing with imperfect detection. We also included, when available, information on important predictors of detection, namely the camera brand and model, use of bait, and obstruction of camera viewshed that can be measured from example pictures at each camera location. Besides its application in studies on the patterns and mechanisms behind occupancy, relative abundance, richness, and detection, the data set presented here can be used to study species' daily activity patterns, activity levels, and spatiotemporal interactions between species. Moreover, data can be used combined with other data sources in the multiple and expanding uses of integrated population modeling. An R script is available to view summaries of the data set. We expect that this data set will be used to advance the knowledge of mammal assemblages and to inform evidence‐based solutions for the conservation of the Atlantic Forest. The data are not copyright restricted; please cite this paper when using the data.

Social-ecological vulnerability to environmental extremes and adaptation pathways in small-scale fisheries of the southern California Current - Fiorenza Micheli; Andrea Saenz-Arroyo; Emilius Aalto; Rodrigo Beas-Luna; Charles A. Boch; Juan Camilo Cardenas; Giulio A. De Leo; Eduardo Diaz; Antonio Espinoza-Montes; Elena Finkbeiner; Jan Freiwald; Stuart Fulton; et al. (Frontiers in Marine Science, 2024)
Coastal ecosystems and human communities are threatened worldwide by climate change, and shocks from social, market and political change. There is an urgent global need to promote resilient food production and livelihoods in the face of these shocks. Small-scale fisheries (SSF) in rural settings can be particularly vulnerable as they frequently lack the resources, rights and infrastructure to respond to shocks originating outside the focal systems. We examined ecological and social outcomes of environmental extremes in a SSF socio-ecological system (SES) by using long-term oceanographic (between 2010-2019) and ecological (2006-2018) data tracking change in a kelp forest ecosystem of Baja California, Mexico, and concurrent documentation of proactive and reactive actions of a fishing community organized in a cooperative. Results indicate a complex landscape of ‘winners’ and ‘losers’ among species and fisheries exposed to unprecedented environmental extremes, including marine heat waves and prolonged hypoxia, and a suite of adaptive actions by the local fishing cooperative, and others in the region, that have helped confront these rapid and drastic changes. Cooperatives have established voluntary marine reserves to promote recovery of affected populations and have invested in diversification of activities enabled by access rights, collective decision-making, and participatory science programs. Results indicate that local actions can support social and ecological resilience in the face of shocks, and that enabling locally-driven adaptation pathways is critical to resilience. This case study highlights the crucial importance of strengthening and supporting rights, governance, capacity, flexibility, learning, and agency for coastal communities to respond to change and sustain their livelihoods and ecosystems in the long run.

Electrogeneration of H2O2 through carbon-based ink on Al foam for electro-Fenton treatment of micropollutants in water - Camilo Rivera-Vera; Manuel A. Rodrigo-Rodrigo; Cristina Saez; Abdoulaye Thiam; Ricardo Salazar-González (Chemosphere, 2024)

Incomplete sanitation in the Metropolitan Region of São Paulo results in detection of SARS-CoV-2 in headwater streams - Ricardo H. Taniwaki; Rodrigo F. Bueno; Giulia B.S. Bispo; Matheus R. Augusto; Guilherme S. Souza; Bruna Chyoshi; Roseli F. Benassi; Nelson Gouveia; Lívia M.B. Camilo; Adriana F.A. Duran; Luís C. Schiesari (Science of The Total Environment, 2024)

Dynamics of biochemical and hormonal reserves degradation in immature seeds of Euterpe edulis Martius (Arecaceae) during in vitro germination - Joana Silva Costa; Tamyris de Mello; Débora Pellanda Fagundes; Ingridh Medeiros Simões; Caroline Palacio de Araujo; Adésio Ferreira; Camilo Elber Vital; Wagner Campos Otoni; José Carlos Lopes; Rodrigo Sobreira Alexandre (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

Subacute high-refined carbohydrate diet leads to abnormal reproductive control of the hypothalamic-pituitary axis in female rats - Jeanini Zimerman; Oscar M.S. Niño; Charles S. da Costa; Jordana F. Zanol; Milena Comério; Letícia N. da Gama de Souza; Leandro Miranda-Alves; Rosiane A. Miranda; Patrícia C. Lisboa; Tays A. Camilo; Rodrigo Rorato; Guilherme Andrade Alves; et al. (Reproductive Toxicology, 2023)

Volatile organic compounds measured by proton transfer reaction mass spectrometry over the complex terrain of Quintero Bay, Central Chile - Rodrigo J. Seguel; René Garreaud; Ricardo Muñoz; Deniz Bozkurt; Laura Gallardo; Charlie Opazo; Héctor Jorquera; Lucas Castillo; Camilo Menares (Environmental Pollution, 2023)

Proteomic profile of stallion seminal plasma - Sandra Fiala-Rechsteiner; Veronica LC Bueno; Edvaldo Barros; Camilo JR López; Pedro MP Vidigal; Humberto JO Ramos; Henrique BA Bastos; Rodrigo C Mattos (Journal of Equine Veterinary Science, 2023)

Upper plate exhumation during continental collision: An example from the paranapanema paleocontinental active margin, SE Brazil - Rodrigo Vinagre Cintra Da Costa; Rudolph Allard Johannes Trouw; Andre Ribeiro; Julio Cezar Mendes; Felipe Tavares; Felipe Nepomuceno; Débora Barros Nascimento; Marcos Ferreira Fontainha; Patrícia Duffles; Camilo Correia Trouw (Journal of South American Earth Sciences, 2023)

Antarctica Slope Front bifurcation eddy: A stationary feature influencing CO2 dynamics in the northern Antarctic Peninsula - Brendon Yuri Damini; Raul Rodrigo Costa; Tiago S. Dotto; Carlos Rafael Borges Mendes; Juan Camilo Torres-Lasso; Marina do V.C. Azaneu; Mauricio M. Mata; Rodrigo Kerr (Progress in Oceanography, 2023)

Birth and growth of the shortnose guitarfish Zapteryx brevirostris (Müller & Henle, 1841) (Chondrichthyes, Rhinobatidae) in captivity - Bruna Larissa Maganhe; Laura de Oliveira Camilo; Rodrigo E. Kurokawa; Hugo Gallo Neto; Eduardo Gomes Sanches (Journal of Fish Biology, 2023)
Endemic to the south‐west Atlantic Ocean, the shortnose guitarfish ( Zapteryx brevirostris ) is a small species, classified as endangered by the IUCN. Although reproduction in captivity has been successful for some species, a range of factors can limit the success of captive breeding programmes for elasmobranchs. In Brazil, the Ubatuba Aquarium was the first public aquarium to reproduce small‐sized elasmobranchs. Since 2018, at least five parturition events have been recorded for Z. brevirostris at the institution. From a total of 13 live neonates that rearing was attempted, the mean ± standard error of weight, total length (TL) and disc width at birth were 17.47 ± 1.6 g, 13.25 ± 0.7 cm and 6.53 ± 0.2 cm, respectively. The mean weight as well as mean TL were higher for females at all births, with 26.15 g and 15.07 cm for females in comparison with 17.09 g and 13.94 cm for males. Considering the increasing risk of extinction that the species is facing, age and growth studies are fundamental for the success of conservation, improving the knowledge of Z. brevirostris life cycle so that a more efficient and sustainable management can be carried out. This study provides important data, as well as directions for captive breeding of the species.

Increased soybean tolerance to high-temperature through biostimulant based on Ascophyllum nodosum (L.) seaweed extract - Rodrigo Alberto Repke; Dayane Mércia Ribeiro Silva; Jania Claudia Camilo dos Santos; Marcelo de Almeida Silva (Journal of Applied Phycology, 2022)

AMAZONIA CAMTRAP: A data set of mammal, bird, and reptile species recorded with camera traps in the Amazon forest - Ana Carolina Antunes; Anelise Montanarin; Diogo Maia Gräbin; Erison Carlos dos Santos Monteiro; Fernando Ferreira de Pinho; Guilherme Costa Alvarenga; Jorge Ahumada; Robert B. Wallace; Emiliano Esterci Ramalho; Adrian Paul Ashton Barnett; Alex Bager; Alexandre Martins Costa Lopes; et al. (Ecology, 2022)
The Amazon forest has the highest biodiversity on Earth. However, information on Amazonian vertebrate diversity is still deficient and scattered across the published, peer‐reviewed, and gray literature and in unpublished raw data. Camera traps are an effective non‐invasive method of surveying vertebrates, applicable to different scales of time and space. In this study, we organized and standardized camera trap records from different Amazon regions to compile the most extensive data set of inventories of mammal, bird, and reptile species ever assembled for the area. The complete data set comprises 154,123 records of 317 species (185 birds, 119 mammals, and 13 reptiles) gathered from surveys from the Amazonian portion of eight countries (Brazil, Bolivia, Colombia, Ecuador, French Guiana, Peru, Suriname, and Venezuela). The most frequently recorded species per taxa were: mammals: Cuniculus paca (11,907 records); birds: Pauxi tuberosa (3713 records); and reptiles: Tupinambis teguixin (716 records). The information detailed in this data paper opens up opportunities for new ecological studies at different spatial and temporal scales, allowing for a more accurate evaluation of the effects of habitat loss, fragmentation, climate change, and other human‐mediated defaunation processes in one of the most important and threatened tropical environments in the world. The data set is not copyright restricted; please cite this data paper when using its data in publications and we also request that researchers and educators inform us of how they are using these data.

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Effects of Microplastics Associated with Triclosan on the Oyster Crassostrea brasiliana: An Integrated Biomarker Approach - Caio Rodrigues Nobre; Beatriz Barbosa Moreno; Aline Vecchio Alves; Jonas de Lima Rosa; Heloisa da Rosa Franco; Denis Moledo de Souza Abessa; Luciane Alves Maranho; Rodrigo Brasil Choueri; Paloma Kachel Gusso-Choueri; Camilo Dias Seabra Pereira (Archives of Environmental Contamination and Toxicology, 2020)

Photocatalytic Properties of Commercially Available TiO2: Study of Fotosan® and InterBrasil® FA-101 for H2S Degradation Using UV and Solar Radiation - Eduardo Borges Lied; Camilo Freddy Mendoza Morejon; Rodrigo Leonardo de Oliveira Basso; Ana Paula Trevisan; Fernanda de Oliveira Tavares; Marcela Boroski; Jacqueline Ferandin Honório (Water, Air, & Soil Pollution, 2020)

Multi-objective optimization of the Brazilian industrial sugarcane scenario: a profitable and ecological approach - Diogo H. Macowski; Lucas Bonfim-Rocha; Rodrigo Orgeda; Rodrigo Camilo; Mauro A. S. S. Ravagnani (Clean Technologies and Environmental Policy, 2020)

Starch accumulation does not lead to feedback photosynthetic downregulation in girdled coffee branches under varying source-to-sink ratios - Rodrigo T. Avila; Samuel C. V. Martins; Lílian M. V. P. Sanglard; Martielly S. dos Santos; Paulo E. Menezes-Silva; Kelly C. Detman; Matheus L. Sanglard; Amanda A. Cardoso; Leandro E. Morais; Camilo E. Vital; Wagner L. Araújo; Adriano Nunes-Nesi; et al. (Trees, 2020)

How do coffee trees deal with severe natural droughts? An analysis of hydraulic, diffusive and biochemical components at the leaf level - Samuel C. V. Martins; Matheus L. Sanglard; Leandro E. Morais; Paulo E. Menezes-Silva; Rafael Mauri; Rodrigo T. Avila; Camilo E. Vital; Amanda A. Cardoso; Fábio M. DaMatta (Trees, 2019)

Physicochemical characteristics of dry aged beef from younger Nellore bulls slaughtered at different body weights - Rodrigo Augusto Cortêz Passetti; Ivanor Nunes do Prado; Francisco de Assis Fonseca de Macedo; Alfredo Jorge Costa Teixeira; Claudia Andréa Lima Cardoso; Gladston Rafael de Arruda Santos; Camilo Azevedo Santos (Tropical Animal Health and Production, 2019)

Modeling abundance, growth, and health of the solitary coral Scolymia wellsi (Mussidae) in turbid SW Atlantic coral reefs - Ericka O. C. Coni; Camilo M. Ferreira; Pedro M. Meirelles; Rafael Menezes; Erika F. C. Santana; Ana Paula B. Moreira; Gilberto M. Amado-Filho; Beatrice P. Ferreira; Guilherme H. Pereira-Filho; Fabiano L. Thompson; Rodrigo L. Moura; Ronaldo B. Francini-Filho (Marine Biology, 2017)

Mesophotic reef fish assemblages of the remote St. Peter and St. Paul’s Archipelago, Mid-Atlantic Ridge, Brazil - Marcos Rogerio Rosa; Aline Cristina Alves; Diego Valverde Medeiros; Ericka Oliveira Cavalcanti Coni; Camilo Moitinho Ferreira; Beatrice Padovani Ferreira; Ricardo de Souza Rosa; Gilberto Menezes Amado-Filho; Guilherme Henrique Pereira-Filho; Rodrigo Leão de Moura; Fabiano Lopes Thompson; Paulo Yukio Gomes Sumida; et al. (Coral Reefs, 2016)

The 16 September 2015 Chile Tsunami from the Post-Tsunami Survey and Numerical Modeling Perspectives - Rafael Aránguiz; Gabriel González; Juan González; Patricio A. Catalán; Rodrigo Cienfuegos; Yuji Yagi; Ryo Okuwaki; Luisa Urra; Karla Contreras; Ian Del Rio; Camilo Rojas (Pure and Applied Geophysics, 2016)

A Critical Comparison of Different Approaches to Sediment-Quality Assessments in the Santos Estuarine System in Brazil - Ronaldo J. Torres; Augusto Cesar; Victor A. Pastor; Camilo D. S. Pereira; Rodrigo B. Choueri; Fernando S. Cortez; Rodofley D. Morais; Denis M. S. Abessa; Marcos R. L. do Nascimento; Cassia R. Morais; Pedro S. Fadini; Tomas A. Del Valls Casillas; et al. (Archives of Environmental Contamination and Toxicology, 2015)

An evaluation of the use of branching fire-corals (Millepora spp.) as refuge by reef fish in the Abrolhos Bank, eastern Brazil - Ericka Oliveira Cavalcanti Coni; Camilo Moitinho Ferreira; Rodrigo Leão de Moura; Pedro Milet Meirelles; Les Kaufman; Ronaldo Bastos Francini-Filho (Environmental Biology of Fishes, 2013)